Effect of whey fat content on the properties and yields of whey cheese and serum - KAMINARIDES, S.; ZAGARI, H.; ZOIDOU, E. (Journal of the Hellenic Veterinary Medical Society, 2020)
The objective of this research was to study the effect of cheese whey fat content on the yield, physicochemical, textural and sensory properties of cheeses made from sheep’s whey. Four types of whey cheese were made from skimmed whey (cheese A), whole whey (cheese B) and whey with added cream of 2.5% and 5% fat (cheeses C and D respectively) and evaluated. Significant differences in yield, sensory properties, total solids, moisture, fat, fat in dry matter, protein, calcium, hardness, modulus of elasticity, gumminess and chewiness were observed between the different types of cheeses. No significant differences were observed in pH, lactose, ash, lactic acid, citric acid, galactose, glucose, Mg, K, Na and cohesiveness. The increase in fat in whey cheeses improved yield, sensory and textural properties. Cheese D was the most preferred of all the experimental cheeses in sensory analysis: it had the highest level of fat in dry matter (77.3%) and the lowest moisture content (51.6%) and according to Greek Food Legislation is characterized as an excellent quality whey cheese. Cheese A had the lowest fat content (3.94%), scored of 61.2% overall in sensory analysis and was characterized as a new reduced-fat whey cheese, particularly suitable for customers who prefer reduced-fat cheese. Serum from whey cheese production should not be considered as a waste but might be exploited as a valuable source of carbohydrate, nitrogenous compounds and minerals. Serum resulting from whey cheese production indicates that it should not be treated as waste-pollutant but as a valuable source of carbohydrate, nitrogenous compounds and minerals from which usable products may be obtained.